Study on the effects of a siddha surgical method in the Management of chronic wounds – case study - Anpuchelvi, S.; Sritharan, G.; Ganesan, S. (Global academic research institute Colombo, Sri Lanka, 2023)
Diabetic ulcers are major health issue worldwide, causing significant economic burdens and affecting both the patient and the society as a whole. Predisposing factors in diabetic patients known as the pathogenic triad, comprise trauma, ischemia, and neuropathy. Regardless of the cause, correct diagnosis and prompt treatment are essential in the management of leg ulcers. Case history We report a case of 45-years old male patient, with a known history of type 2 diabetes mellitus who presented to our hospital with of non-healing wounds over the left sole of the foot with a gangrenous over a period for two months. When he came to our clinic, he was already advised to left foot amputation to avoid further complications. After careful examination of wound it was found that the wound was irregular in shape with unhealthy granulation tissue. On further inspection the surrounding areas of wound shows inflammatory changes with unpleasant foul-smelling watery discharges. So, our main aim was to treat the impending diabetic condition and prevent the foot from amputation which came as a major challenge. To remove harmful microorganism, wound was cleaned with Triripala decoction (Herbal antiseptic lotion). Then Probe was introduced in the fistula region. In the technique, a specially prepared medicated thread known as “Kshara sutra” (Medicated alkaline thread) is used. This sterilized thread is repeatedly soaked in solution of Herbal Medicine (Figures I and II). Another wound also covered by the Kshara gauze. Bandaging was done moderately while external herbal applications were applied to the wound area. A multidisciplinary holistic approach must be used when treating diabetic foot ulcers. Different modalities and sessions of debridement should be performed after optimizing the general condition of the patient.
Keywords: Tripala decoction; Kshara sutra; Herbal Medicine